Analysis of the development of environmental design As part of design and survey work ("Journal "U". Economy. Management. Finance.", 2023)
The article examines the current state of environmental design and its impact on design and survey work, including new environmental technologies and materials. The main purpose of the article is to analyze trends and prospects for the development of environmental design in the framework of design and survey work.
Keywords: environmental design; design and survey work; development analysis; construction; management; legislation; standards; environmental protection